Analisis Tindak Tutur Lokusi Podcast Bertema Pengembangan Diri dalam Saluran Spotify Andreass Bordes - Neri Vedita Putri; Wilda Robiatul Mahbubah; Eva Annisa Riska; Adhela Fathma Setyani; Efriza Kharidatul Bahiyah; Akhmad Faqih Khaerussani; Asep Purwo Yudi Utomo; Ahmad Fajar Habibi (Populer: Jurnal Penelitian Mahasiswa, 2025)
This study explores the use of locutionary speech acts in the podcast “Self-Development” by Andreass Bodres which is currently popular on the spotify application. Podcasts as digital audio media have become a forum for various discussions, including the topic of self-development. The methodological approach and theoretical approach are applied as an approach to the analysis of this research. Methodological approach uses a qualitative descriptive method, and the theoretical approach in analyzing speech acts uses analytical methods in the field of pragmatics. Locutionary speech acts, which are related to the literal meaning of an utterance, are considered crucial in conveying messages effectively in the context of podcasts. This study aims to identify the dominant types of locutionary speech acts in the podcast, and to analyze how these speech acts contribute to building the narrative and inspiring listeners. By analyzing the podcast transcripts, this research is expected to provide a deeper understanding of the communication mechanisms in self-development podcasts. The analysis results contained in the 6 “Self Development” podcasts on Andreas Bodres' spotify channel include 13 declarative or news speech acts, 6 questioning speech acts, and 15 reminding speech acts. To produce 34 data in the form of locutionary speech acts. This research is expected to contribute to the knowledge and insight of researchers about the analysis of speech acts carried out on the “Self Development” podcast on Andreas Bodres' spotify channel. This research is expected to contribute to the field of linguistics, especially pragmatics, and provide insight for podcast creators, listeners, and other researchers. In addition, this study also reveals how the context and purpose of communication affect the choice of speech acts used, as well as their impact on audience understanding and engagement.